Prayers and Mindfulness in Relation to Mental Health among First-Generation Immigrant and Refugee Muslim Women in the USA: An Exploratory Study - Callender, Karisse A. (Journal of religion and health, 2022)
The goal of our study was to explore how first-generation immigrant/refugee Muslim women experience prayer and mindfulness in relation to their mental health. Participants were nine women from an urban city in the Midwestern USA. The women completed a structured demographic survey and a virtual semi-structured interview in a focus group. Using qualitative thematic analysis, we obtained four overarching themes from the data: (a) Prayer helps to build community, (b) Prayer promotes wellbeing, (c) Prayer increases faith, and (d) Prayer encourages intentional awareness. The findings demonstrate that prayer involves awareness and has a strong influence on the mental health of the women participants.